2009
DOI: 10.1287/isre.1090.0236
|View full text |Cite
|
Sign up to set email alerts
|

Agility from First Principles: Reconstructing the Concept of Agility in Information Systems Development

Abstract: Awareness and use of agile methods has grown rapidly among the information systems development (ISD) community in recent years. Like most previous methods, the development and promotion of these methods have been almost entirely driven by practitioners and consultants, with little participation from the research community during the early stages of evolution. While these methods are now the focus of more and more research efforts, most studies are still based on XP, Scrum, and other industry-driven foundations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
431
1
27

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 579 publications
(510 citation statements)
references
References 107 publications
(136 reference statements)
4
431
1
27
Order By: Relevance
“…In the references in Chuang et al [13] we found no papers on the topic of business value (searching on 'value'); eight discussing measurement ('metrics', 'measurement'); and none on claims or limitations ('misconception', 'shortcoming', 'fail', 'hype', 'lack', 'claim', 'limitation'). While there is some literature about the concept of agility [6,41], there is very little about misconceptions, hype and failure. Agile hype is discussed by Janes and Succi [42] who suggest agile has followed the Gartner Hype Cycle, and is stuck in the 'Trough of Disillusionment' as a result of what they call the 'guru phenomenon'.…”
Section: Which Challenges Are Being Addressed By Research?mentioning
confidence: 99%
“…In the references in Chuang et al [13] we found no papers on the topic of business value (searching on 'value'); eight discussing measurement ('metrics', 'measurement'); and none on claims or limitations ('misconception', 'shortcoming', 'fail', 'hype', 'lack', 'claim', 'limitation'). While there is some literature about the concept of agility [6,41], there is very little about misconceptions, hype and failure. Agile hype is discussed by Janes and Succi [42] who suggest agile has followed the Gartner Hype Cycle, and is stuck in the 'Trough of Disillusionment' as a result of what they call the 'guru phenomenon'.…”
Section: Which Challenges Are Being Addressed By Research?mentioning
confidence: 99%
“…Stephens & Rosenberg, 2003). While this view has been contradicted by some, Conboy (2009) suggests that this may not be the case, pointing to the significant volume of research attempting to rebuild and tailor these methods so they can operate in other environments (e.g. Bowers et al, 2002;Crispin & House, 2003;Stotts et al, 2003;Cao et al, 2004;Kahkonen, 2004;Lindvall et al, 2004).…”
Section: Current Shortcomings In Agile Systems Development Researchmentioning
confidence: 99%
“…The ongoing debate on agile vs. plan-driven methods reflects a lack of understanding of agile concepts and how agile software development is conducted in practice, which can be attributed in part to the weak theoretical grounding of agile methods (Turk et al 2002, Conboy andFitzgerald 2004) and further conceptual problems such as lack of clarity and lack of "theoretical glue" (Conboy 2009). These issues raise the concern that agile methods may be "reduced to a series of steps executed by rote" (Highsmith 2000, p.14).…”
Section: Introductionmentioning
confidence: 99%